2016
DOI: 10.1039/c6ra20472d
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-assisted polymerase chain reaction: effects of surface ligands, nanoparticle shape and material

Abstract: The concentration, shape, material, and surface functionalization effects of gold nanoparticles on PCR outcome have been studied with two PCR gene diagnostic models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…These PCR results confirm that the immobilized oligonucleotides on the gold nanoparticle surfaces maintain their accessibility to perform PCR contributing also to reducing the presence of unspecific bands. This effect was also described previously for the detection of the nitrogen fixation gene in Azospirillum bacteria and for other DNAs [16,17,18]. Taken together, here we demonstrated that an oligonucleotide anchored to the Au@SiO2–COOH is accessible for further recognition by methylated DNA of RPRM .…”
Section: Resultssupporting
confidence: 88%
“…These PCR results confirm that the immobilized oligonucleotides on the gold nanoparticle surfaces maintain their accessibility to perform PCR contributing also to reducing the presence of unspecific bands. This effect was also described previously for the detection of the nitrogen fixation gene in Azospirillum bacteria and for other DNAs [16,17,18]. Taken together, here we demonstrated that an oligonucleotide anchored to the Au@SiO2–COOH is accessible for further recognition by methylated DNA of RPRM .…”
Section: Resultssupporting
confidence: 88%
“…It exploits the light-to-heat conversion mediated by plasmonic substrates [26][27][28][29] . This concept has been adopted for PCR thermocycling, in the form of a planar plasmonic substrate in a fluidic device 20,30,31 or metallic nanoparticles in suspension 22,32,33 . Both methods have shown fast nucleic acid ampli-fication, but challenges remain: nucleic acids after amplification are difficult to detect because plasmonic substrates would interfere with fluorescence reporters 34,35 .…”
mentioning
confidence: 99%
“…[ 11,39,40 ] In the meantime, some other characters of nanoparticles may also influence the PCR amplification, such as surface ligands, nanoparticle shape, and material. [ 41 ] Therefore, the true processes that occur in the nano‐localized environment during NA amplification still need to be explored, which is critical to optimize the nano‐localized NA amplification.…”
Section: Discussionmentioning
confidence: 99%